Influence of magnetically treated water on blood biochemical parameters in beef cattle - Silva , Allan Leon Casemiro da; Gabriel, Camila Pires Cremasco; Putti, Fernando Ferrari; Chacur, Marcelo George Mungai; Gabriel Filho, Luís Roberto Almeida; Andrade, Isamara Batata (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
As with any technology to increase productivity in beef cattle, good herd management and improvement practices must be integrated to obtain superior quantitative and qualitative productivity rankings. Therefore, this study aimed to verify the effects of the use of magnetically treated water on productive parameters of beef cattle, especially animal blood biochemistry, final weight, and carcass finishing traits. A comparison was performed with a group of 10 animals in the state of São Paulo, Brazil. The use of magnetically treated water (MTW) did not influence the improvement in the blood biochemical indices of animals regarding the variables potassium (K), ionic calcium (iCa), chlorine (Cl), and cholesterol. The MTW group presented a 1.2% concentration index for the variable sodium (Na) in the blood compared to the control group.